2012
DOI: 10.1016/j.jcm.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of pulse oximetry in chiropractic practice: a rationale for its use

Abstract: Objective: Pulse oximetry is used regularly to assess oxygen saturation levels. The objective of this commentary is to discuss a rationale for using pulse oximetry in chiropractic practice. Discussion: Pulse oximetry may offer doctors of chiropractic a way to monitor patients' oxygen saturation levels. Quantification of saturation values with heart rate may give clinical aid to the management of chiropractic patients. Markedly reduced saturation levels may necessitate medical referral, whereas mildly reduced l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…They are assigned to review a number of prominent skeptics and their critique and research of CAM, for example: "Whither Chiropractic?" (Hall, 2019b), "How thinking goes wrong" (Shermer, 1994), Homeopathy (Randi, 1982), Quackwatch: Your Guide to Quackery, Health Fraud, and Intelligent Decisions (Barrett, 2021), and "Traditional Medicine and Pseudoscience in China: A Report of the Second CSICOP Delegation" (Beyerstein & Sampson, 1996). Although many students come loaded with discomfort about the WBM from their personal experiences, it is important for them to balance that by learning there is deceit and fraud in many places in medicine, including in CAM, and it is important to know how to detect it (Synovitz & Larson, 2018, pp.…”
Section: Science's Semi-permeable Membranementioning
confidence: 99%
“…They are assigned to review a number of prominent skeptics and their critique and research of CAM, for example: "Whither Chiropractic?" (Hall, 2019b), "How thinking goes wrong" (Shermer, 1994), Homeopathy (Randi, 1982), Quackwatch: Your Guide to Quackery, Health Fraud, and Intelligent Decisions (Barrett, 2021), and "Traditional Medicine and Pseudoscience in China: A Report of the Second CSICOP Delegation" (Beyerstein & Sampson, 1996). Although many students come loaded with discomfort about the WBM from their personal experiences, it is important for them to balance that by learning there is deceit and fraud in many places in medicine, including in CAM, and it is important to know how to detect it (Synovitz & Larson, 2018, pp.…”
Section: Science's Semi-permeable Membranementioning
confidence: 99%
“…We appreciate that there is interest in our technical article. 1 It appears to us that 3 points are being raised about our article. It is being suggested that (1) our use of the Roth and Holtmann reference does not support our statement that "pulse oximetry is indicated because hypoxia is commonly found in the elderly," (2) that our use of the article by Sommermeyer et al does not support our "position that pulse oximetry is indicated in hypoxia-related disorders," and (3) that our use of the Braun chapter does not "support (our alleged) contention that pain is an indicator for pulse oximetry.…”
mentioning
confidence: 94%
“…One of the vital signs is heart rate (HR). The value of HR can describe your level of fitness [6]. HR is important to be monitored in the normal condition, but in the training condition is more important [7].…”
Section: Introductionmentioning
confidence: 99%